Jaburan Tradition under Islamic Customary Jurisprudence: Legitimizing Local Religious Practices in Rural Mosques - Ari Maulana Ramadan; Imam Aris Utomo; Qodim Ma’shum (CV. Era Digital Nusantara, 2026)
This article examines the profound dialectical tension between Islamic law universality and socio-cultural particularity through the jaburan tradition in rural Javanese mosques. Utilizing a socio-legal approach, this study thoroughly integrates doctrinal jurisprudence analysis with empirical field research to evaluate the structural institutionalization of this daily communal practice. The findings demonstrate that jaburan operates not merely as sporadic philanthropy, but as a strictly binding cultural social contract proactively governed by local mosque authorities. Through the strict application of the al-'adah al-muhakkamah maxim, this localized tradition is definitively validated as 'urf shahih 'amali, successfully harmonizing local Javanese philosophies of social cohesion with the fundamental objectives of Islamic law. Consequently, this grassroots institutionalization ultimately exemplifies a functional legal pluralism paradigm wherein micro-level living sharia proves significantly more resilient and adaptable than rigid top-down state law codification in preserving religious identities within an increasingly complex global societal order without triggering any harmful doctrinal deviations.